Fat forward: Cultivating bovine adipocytes on bioscaffolds - Apeksha Bharatgiri Goswami; Joanna M. Biazik; Johannes le Coutre (Current Research in Food Science)
The advancement of cellular agriculture hinges on replicating the mouthfeel, taste, and texture of conventional meat, which are largely determined by fat tissue composed of adipocytes. However, growing cells at scale remains a significant challenge for the field. This study explores the use of edible bioscaffolds to support the large-scale production of bovine adipocytes.Scaffold-based approaches are commonly used to facilitate the proliferation of adherent cells within bioreactors, yet identifying suitable, edible scaffolds for cultured meat remains an ongoing challenge. Here, we present an efficient approach for screening biological scaffolds and evaluating their suitability for cultured meat production. We assess whole oats and unhulled buckwheat as potential substrates for bovine preadipocyte attachment, proliferation, and differentiation. Our results demonstrate that both grains support cell adhesion and growth; however, with their favourable surface properties, whole oats emerged as a promising natural bioscaffold for cultured food applications, offering both scalability and nutritional benefits.